Novel thermodynamic model for simulation of hydrogen/diesel fueled PCCI engine - Ghasem Jalivar; Elaheh Neshat (Heliyon)
Utilizing hydrogen as an environmentally friendly fuel in LTC engines, which are ultra-low emission engines, enhances efficiency and improves combustion phase control. This addresses environmental challenges posed by fossil fuels. Effective control of the combustion phase in LTC engines, considering factors like fuel type, injection timing, and EGR percentage, requires real-time control-oriented models to optimize engine performance. However, CFD models face significant challenges in this area. This study introduces a thermodynamic-empirical model for simulating hydrogen/diesel dual-fuel PCCI combustion with minimal calibratable parameters. The model, developed in EES software, is validated using experimental data. The model's MFB curves, CA50, and IMEP values are compared with experimental results. Additionally, the model's results are compared with a previously validated CFD model's results for the 1.9L GM engine, including pressure, temperature, MFB curves, IMEP, and thermal efficiency values. Validation results show average errors of 0.25 CAD for CA50 and 0.043 bar for IMEP. Verification results indicate a highest percentage difference in peak pressure of 3.85 % and an average error in peak pressure timing of 0.6 CAD. The average error of CA50 between the presented model and the CFD model is 1.28 CAD, indicating the Wiebe function accurately simulates the PCCI combustion phase. The highest percentage difference in IMEP and the average error in thermal efficiency between the thermodynamic model and CFD results are 2.7 % and 2.41 %, respectively. The validation and verification results demonstrate the model's high accuracy and reliability, making it suitable for control applications of hydrogen/diesel dual-fuel PCCI combustion and a powerful tool for researching and developing hybrid systems, including PCCI engines, as environmentally friendly systems.